Slip Effects on Peristaltic Transport in an Inclined Channel with Mass Transfer and Chemical Reaction - T. Hayat; Humaira Yasmin; S. Asghar; Awatif A. Hendi (Applied Bionics and Biomechanics)
An analysis is carried out for the peristaltic flow in an inclined asymmetric channel when no-slip condition does not hold. The whole analysis has been carried out in the presence of mass transfer and chemical reaction. The channel asymmetry is generated because of peristaltic wave train on the walls through different amplitudes and phases. Long wavelength and low Reynolds number assumption is adopted in the whole mathematical analysis. Expressions for the stream function and longitudinal pressure gradient have been developed. Numerical integration is performed for the analysis of pressure rise per wavelength. Longitudinal velocity, pumping and trapping phenomena are analyzed in detail via plots.